2019
DOI: 10.1038/s41598-019-53915-7
|View full text |Cite
|
Sign up to set email alerts
|

An epigenetic screening determines BET proteins as targets to suppress self-renewal and tumorigenicity in canine mammary cancer cells

Abstract: Targeting self-renewal and tumorigenicity has been proposed as a potential strategy against cancer stem cells (CSCs). Epigenetic proteins are key modulators of gene expression and cancer development contributing to regulation and maintenance of self-renewal and tumorigenicity. Here, we have screened a small-molecule epigenetic inhibitor library using 3D in vitro models in order to determine potential epigenetic targets associated with self-renewal and tumorigenicity in Canine Mammary Cancer (CMC) cells. We ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 74 publications
(84 reference statements)
1
14
0
Order By: Relevance
“…Recently, we observed that the inhibition of bromodomain and extraterminal (BET) family of proteins, an epigenetic reader of histone acetylation, using (+)-JQ1, is a promising strategy to inhibit self-renewal and tumorigenicity in CMC cells using 3D in vitro models. Low concentrations of (+)-JQ1 inhibited tumorsphere and colony formation and were able to downregulate important genes associated with selfrenewal pathways including WNT, NOTCH, Hedgehog, and PI3K/AKT/mTOR (Xavier et al, 2019). These results strongly indicated that BET inhibition modulates malignant phenotypes such as self-renewal and could directly impact tumorigenic cells such as cancer stem cells (CSCs) in CMC cells.…”
Section: Open Accessmentioning
confidence: 83%
“…Recently, we observed that the inhibition of bromodomain and extraterminal (BET) family of proteins, an epigenetic reader of histone acetylation, using (+)-JQ1, is a promising strategy to inhibit self-renewal and tumorigenicity in CMC cells using 3D in vitro models. Low concentrations of (+)-JQ1 inhibited tumorsphere and colony formation and were able to downregulate important genes associated with selfrenewal pathways including WNT, NOTCH, Hedgehog, and PI3K/AKT/mTOR (Xavier et al, 2019). These results strongly indicated that BET inhibition modulates malignant phenotypes such as self-renewal and could directly impact tumorigenic cells such as cancer stem cells (CSCs) in CMC cells.…”
Section: Open Accessmentioning
confidence: 83%
“…We observed three inhibitors inducing significant reduction of cell viability in CMCs including (+)-JQ1 (BET family inhibitor), NVS-CECR2-1 (CECR2 inhibitor), and UNC1999 (EZH2/1 inhibitor). Furthermore, BET inhibition by (+)-JQ1 was very efficient to inhibit CMCs colony and tumorsphere formation, demonstrating an effect on tumorigenicity and self-renewal ( Figure 3) (222). Inhibition of SET methyltransferase by shRNA and FTY720, reported to directly interact with SET proteins, suppressed cell proliferation, colony formation, and in vivo tumor growth of canine mammary and osteosarcoma cell lines.…”
Section: Alternative Epigenetic Targetsmentioning
confidence: 91%
“…The (+)-JQ1 (BET family inhibitor), NVS-CECR2-1 (CECR2 inhibitor), and UNC1999 (EZH2/1 inhibitor) decreased cell viability of CF41.Mg canine mammary cancer cell line. Furthermore, (+)-JQ1 exhibits a strong impact on colony and tumorspheres formation, demonstrating effects on tumorigenicity and self-renewal phenotypes (222). canine mammary cancer cells, activating endoplasmic reticulum stress pathway in these cells (225).…”
Section: Alternative Epigenetic Targetsmentioning
confidence: 99%
“…Mammary cancer cell lines were validated previously by global gene expression 8,11 and by attesting the origin of cell lines by amplification and sequencing of fragments from cytochrome oxidase I (COI) and 16S 11 …”
Section: Methodsmentioning
confidence: 99%